Identification of a resident community of bottlenose dolphins (Tursiops aduncus) in the Swan Canning Riverpark, Western Australia, using behavioural information - Chabanne, D.; Finn, H.; Salgado Kent, Chandra; Bejder, L. (Surrey Beatty and Sons, 2012)
Identifying appropriate management units is vital for wildlife management. Here we investigate one potential management unit – resident communities of bottlenose dolphins – using information from ranging, occupancy, and association patterns. We identify a resident community of Indo-Pacific bottlenose dolphins (Tursiops aduncus) in the Swan Canning Riverpark, Western Australia based on: ranging patterns, sighting rates, Lagged Identification Rates (LIR), and three measures of social affinity and structure (Simple Ratio Index, preferred dyadic association analyses, and Lagged Association Rates (LAR)). The analyses yielded an estimated ‘community size’ of 17-18 individuals (excluding calves). High seasonal sighting rates (>0.75 sightings per season) and a long mean residence time (ca. nine years) indicated year-round residency. The model best-fitting the LIR (emigration and mortality) also supported this. The social structure of dolphins was species-typical, characterized by significant dyadic associations within age-sex classes (permutation test; P < 0.001), stronger associations among adult males than among adult females (LAR males > LAR females), and temporally stable associations (LAR > null LAR). Constant companions or long-lasting association models best explained adult male and female LARs. While behavioural information identified a resident community in the Riverpark, genetic and demographic information is needed to assess its appropriateness as a management unit.